Nihilation of femininity in the battle of looks: a Sartrean reading of Jhumpa Lahiri’s “A temporary matter” - Asl, Moussa Pourya; Hull, Simon Peter; Nurul Farhana Low Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2016)
The panoptic gaze is vested in with a constitutive impact upon the subjectivity of individuals. Feminist scholars like Luce Irigaray have charged that the metaphor of vision is intimately connected with the construction of gender and sexual difference. By pointing to the masculine logic of Western thought, Irigaray confirms that a woman’s entry into a dominant scopic economy signifies her inevitable confinement to passivity. This essay aims to examine the sexual politics of metaphors of vision in a literary text that is controversially argued to be a voice for the subordinated Indian immigrant women in the US. As one of the most influential schools of thought in Western philosophy, the Sartrean paradigm of sexual difference is employed to investigate this allegation by identifying the latent binary system at work in the fiction of Jhumpa Lahiri, who has garnered substantial yet controversial critical attention over her representations of gender. Specifically, this essay focuses on Lahiri’s prefatory story to her Pulitzer Prize-winning short story collection, Interpreter of Maladies (2000), to unravel the manner her exercise of vision in this narrative perpetuates the dichotomies of a male subject and a female object pre-established in the traditional hierarchies of gender in the West. In this story, Lahiri (un)wittingly privileges masculinity over femininity and reduces the latter to a typically disgusting Sartrean female body of holes and slime. Hence, notwithstanding infrequent emasculated images of the male subject, it is ultimately the masculine that, in the battle of looks between male and female, nihilates the Other to the state of “being-in-itself” and enjoys supremacy over the feminine.